Public Space and Urban Agroecology. Genealogies and Strategies of Landscape Integration in Rosario, Argentina - Roldán, Diego (2025)
This article explores how urban agriculture in Rosario challenges hegemonic discourses on landscape and territory, proposing some keys to rethink green public space. The city of Rosario is selected as a case study due to the relevance and recognition of its agroecology. The methodology consists of a critical interpretation of documentary sources, an analysis of personal interviews with key informants and a direct observation of agroecological devices. For this purpose, the origins of urban agriculture are investigated and its links with economic crises and urban peripheries are shown. Then, the trajectory of green landscapes privileged by public spaces is analyzed to show the historical dissociation between the imaginaries of aesthetics-recreation and production-environment. Finally, the potentialities of orchard parks and agroecological fairs are addressed in order to establish synergies between agroecology and public space and to inscribe agroecological landscapes in urban centralities. Both devices exhibit capacities to integrate production and consumption, ecological landscapes and, ultimately, to reassemble the relationship between nature and city.